Therapeutic modalities for superior sulcus tumor (Pancoast) tumor – A systematic review - Langer, Susan; Medenwald, Daniel; Vordermark, Dirk; Schuette, Wolfgang; Deppermann, Karl-Matthias; Nothacker, Monika; Eggeling, Stephan; Efremov, Ljupcho (Lung cancer (Amsterdam, Netherlands), 2025)
•Review on studies with mono-, bi- or trimodal treatment on sulcus superior tumors (1990–2024)•Thirty-five studies included (28 retrospective, 7 prospective), with follow-up of 10–107 months.•Trimodal therapy associated with better survival and lower rates of distant metastases.•Studies considering immunotherapy are still missing. Superior sulcus tumors (SST) are usually treated with multimodal therapy, mainly trimodal therapy encompassing radiochemotherapy (CRT) followed by surgery. However, high-level evidence from randomized trials remains limited. We conducted a systematic review to assess the evidence of treatment strategies considering adverse events and oncologic outcomes. We systematically searched MEDLINE, CINAHL, EMBASE, Web of Science, CENTRAL, grey literature databases, and clinical trial registries. We included prospective and retrospective studies published between 1990 and 2024 with mono-, bi- or trimodal treatment reporting outcomes such as overall survival (OS), progression-free survival (PFS), resection rates, postoperative mortality/morbidity, and adverse events. Studies required histologically confirmed SST and a minimum of 30 patients. Thirty-five studies were included (28 retrospective, 7 prospective), with follow-up ranging from 10 to 107 months. Most studies originated from Europe (n = 16) and North America (n = 14). Sample sizes ranged from 30 to 2910 patients, predominantly male and aged in the late 50s to early 60s. Induction CRT protocols varied widely. R0 resection rates were reported in 33 studies, and trimodal therapy outcomes in 12. Hematotoxicity and esophagitis were the most common adverse events. Five-year OS rates varied between 11.8 % and 77 %, with trimodal therapy associated with better survival and distant metastasis as the dominant recurrence pattern. There were no studies addressing immunotherapy. While trimodal therapy remains the guideline-endorsed standard for SST, comparative evidence remains sparse. The role of immunotherapy in induction regimens warrants further investigation.